Radical Surgery of Only the Anterior Elements of the Spine at the Posterior Element Fusion Level due to Metastatic Thyroid Cancer. (27th June 2017) - Tsuchiya, Ryuto; Fujimoto, Kazuki; Inage, Kazuhide; Orita, Sumihisa; Shiga, Yasuhiro; Kamoda, Hiroto; Yamauchi, Kazuyo; Suzuki, Miyako; Sato, Jun; Abe, Koki; Kanamoto, Hirohito; Inoue, Masahiro; et al.
Abstract : Spinal metastasis of differentiated thyroid cancer can have a favorable prognosis if radical surgery is performed. We encountered a case of spinal metastasis involving three anterior vertebral bodies at the posterior element fusion level and successfully achieved adequate stability by radical surgery involving only the anterior elements. A 67-year-old woman who had numbness and muscle weakness in the lower limbs caused by metastatic spinal tumor at the posterior element fusion level of L1–L3 vertebrae was treated with radical surgery of only the anterior element to gain stability. Similar situations may occur in cases involving other malignant tumor metastases or spinal primary tumors. If such a case occurs, this method could be useful in preventing metastasis to the posterior element.